PRARANCANGAN PABRIKMETIL TERT BUTIL ETER DARI METANOL DAN ISOBUTENE KAPASITAS 550.000 TON/TAHUN - Hendratama, Handik (2017)
Methyl tert-butyl ether (MTBE) is an additive used in the process of production fuel. In order to maintain the stabi of stability in the availability of energy, especially fuel, Indonesia still have to import to the additive. To serve domestic needs as well as great export opportunities against this type of product, then designed the mill establishment of MTBE from isobutene and methanol with a capacity of 550,000 tonnes/year. The factory will be planned to be established in Bontang industrial area, precisely in the District of North Bontang, East Kalimantan Bontang District. MTBE is produced by reacting methanol with isobutene. As a result of the incoming feed is not purely, the side reaction occurs, namely the establishment of Tert Butyl Alcohol (TBA). To increase the total reaction conversion, so the 25509.7196 kg/hour feed methanol input added with water 489.9194 kg/h in a mixer. So that the methanol feed come into the reactor with a weight fraction of 98%. Because the reaction nature is reversible, so the feed methanol excess of 10%. Feed isobutene as much 47046.4127 kg/h with a purity of 99.95% and feed out mixer enter into a fixed bed multitube reactor with catalyst Amberlyst 15, Temperatur 70°C, pressure of 10 atm, reversible and exothermic. Then the product was purified using three distillation tower to obtain a final product purity above 99%. In order to support the production process, it is required process water and other needs as much as 31,306,291 kg/day and steam needs as much 11069.4030 kg/day, supported by three generators as electric power as much as 2.2987 MW. Company form which is used is a Limited Company (PT). Working system imposed in factory, in the form of shift and non-shift with a number of employees as much as 291 people. The MTBE factory uses a total production cost of Rp. 8,973,133,319,146 Return of Investment value is 1.455% and 1.164% before and after tax respectively. Pay OutTime are 6.00 years and 6.12 years before and after tax respectively. Break Even Point is 41.9605%. Shut Down Point is 31.5909%. Based on the economic analysis, the establishment of this MTBE factory is worth considering to be establishment. Kerywoard : Methyl tert butyl eter, tert butyl alcohol